1989
DOI: 10.1111/j.1439-0264.1989.tb00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Radiological Observations of the Sesamoid Bone of the Popliteus Muscle in the Adult Dog and Cat

Abstract: In a random selection of 50 adult dogs (25 males and 25 females) and 50 adult cats (25 males and 25 females), the incidence of ossification of the sesamoid structure of the popliteus muscle was characterized through anatomical dissection and radiographic techniques. The incidence of ossification was 84% in the dogs and 100% in the cats. In both anatomical and radiologic studies, it was demonstrated that when the knee was fully extended, the sesamoid bone was adjacent to the caudodistal part of the articular su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
(1 reference statement)
2
9
0
Order By: Relevance
“…The large ovoid popliteal sesamoid bone observed in this study appears similar to that of domestic cats (McCarthy and Wood, ). The absence of visualization of the popliteal sesamoid bone on radiographic examination in some of the animals in this study is similar to a reported study in domestic cats (Arnbjerg and Heje, ).…”
Section: Discussionsupporting
confidence: 82%
“…The large ovoid popliteal sesamoid bone observed in this study appears similar to that of domestic cats (McCarthy and Wood, ). The absence of visualization of the popliteal sesamoid bone on radiographic examination in some of the animals in this study is similar to a reported study in domestic cats (Arnbjerg and Heje, ).…”
Section: Discussionsupporting
confidence: 82%
“…Cyamella is commonly seen in certain other mammalian species, with a prevalence of 100% in cats and 84% in dogs. Distal displacement of a cyamella in dogs has even been proposed as a potential secondary sign of ligamentous injury ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been performed regarding sesamoids in mammals, but unevenly distributed among clades and sesamoids. The best studied orders are Rodentia, mainly Mus musculus as a model organism (Pedersen, ; Wirtschafter & Tsujimura, ; Ralphs et al, ; Ralphs, Tyers & Benjamin, ; Doherty et al, ; Koyama et al, ; Eyal et al, , a , b ; Abella et al, ), Primates (Jungers et al, ; Walji & Fasana, ; Le Minor, , , ; Sarin et al, ), mainly focused on Homo sapiens within a clinical framework (see Section V), and Carnivora (Carey et al, ; Vaughan & France, ; McCarthy & Wood, ; Arnbjerg & Heje, ; Červený & Páral, ; Endo et al, ; Kirberger et al, ; Walker et al, ; Antón et al, ; Salesa et al, ; Abella et al, ). Surprisingly, aquatic mammals with their highly divergent skeletons have been largely ignored within the sesamoid literature.…”
Section: Sesamoids In Tetrapodamentioning
confidence: 99%
“…Wood‐Jones, ; Le Minor, ; Endo et al, ; Sánchez‐Villagra & Menke, ; Antón et al, ; Salesa et al, ; Hutchinson et al, ; Mitgutsch et al, ; Abella et al, , ), the cyamella (located in the tendon of the m. popliteus) and fabellae (located in the tendon of the m. gastrocnemius) (e.g. McCarthy & Wood, ; Le Minor, ; Arnbjerg & Heje, ; Červený & Páral, ; Sarin et al, ; Salas et al, ). It has been proposed that fusion of the cyamella and fabella produced the parafibula (Pearson & Davin, ).…”
Section: Sesamoids In Tetrapodamentioning
confidence: 99%